qanda-logo
search-icon
Símbolos
Problema
solution-image
A) $\left(5x^{3}$ $-3y^{2}\right)^{2}=$ $B\right)$ $\left(6a^{3}b^{4}+4ab^{2}\right)^{2}=$ $\right)\left(\dfrac {1} {2}m^{5}-\dfrac {4} {3}\right)^{2}=$ D) $\right)$ $\left(2a^{2}-8\right)^{3}=$ E) $\right)$ $\left(3x^{2}y^{3}$ $-4x^{2}y^{2}\right)^{3}=$ F) $\right)$ $\left(6x^{4}y^{5}z^{6}+12xy^{2}z^{3}$ $\right)\left(6x^{4}y^{5}z^{6}-12xy^{2}z^{3}\right)=$ $5\right)\left(10a^{6}b^{4}+2c^{3}\right)\left(10a^{6}b^{4}$ $-2c^{3}\right)=$
Bachillerato
Aritmética y álgebra
Búsquedas: 153
Contenido de la pregunta
resolver y desglosarlo porfa
Solución
answer-user-profile-image
Profesor de Qanda - Rubén
answer-reply-image